The Effect of Information Technology Utilization, Human Resource Quality, and the Role of Organizational Commitment on the Quality of Financial Statements of PT. Dua Kelinci - Marcella Hemalia Anggraini; Eskasari Putri (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
The purpose of this study was to analyze the effect of information technology utilization, the quality of human resources, and the role of organizational commitment on the quality of PT Dua Kelinci's financial statements. This research method is quantitative. The population in this study were employees of PT. TWO KELINCI. The sample technique used in this study was to conduct a survey. The number of research samples was determined using the Slovin formula, based on this formula, the number of samples obtained was 96. The type of data used is primary data. The data collection technique uses two approaches, namely interviews and questionnaires. The data analysis techniques used in this research are multiple linear regression analysis and moderated regression analysis. Data quality checks and classical assumption tests must be completed before performing regression analysis to verify that the regression model meets valid requirements, namely reliability, normality, multicollinearity, autocorrelation, and heteroscedasticity. The result of this study is that the utilization of information technology has a positive effect on the quality of financial statements. The quality of human resources has a positive effect on the quality of financial reports. The role of organizational commitment has a positive effect on the quality of financial reports.